Avoidance of suspended sediment by the juvenile migratory stage of six New Zealand native fish species - Jacques A. T. Boubée; Tracie L. Dean; David W. West; Rhys F. G. Barrier (New Zealand Journal of Marine and Freshwater Research, 1997)
The avoidance response of the migratory juvenile stage of six species of diadromous fish to different levels of suspended solid (SS) was determined in the laboratory using a two‐choice avoidance tank. Trials were mostly conducted with resuspended sediment from the outlet of Lake Waahi, New Zealand, but a series of tests was also conducted with kaolin for comparison. Banded kokopu (Galaxias fasciatus) was the most sensitive species, displaying a 50% avoidance response to kaolin and Waahi silt at 17 and 25 NTU, respectively. Koaro (Galaxias brevipinnis) and inanga (Galaxias maculatus) were found to be less sensitive than banded kokopu, with a 50% avoidance response to Waahi silt at 70 and 420 NTU, respectively. Shortfinned and longfinned elvers (Anguilla australis and/1, dieffenbachii) , and redfinned bullies (Gobiomorphus huttoni) showed no avoidance behaviour, even at the highest turbidities (1100 NTU) tested. Based on these laboratory results, and until field testing is undertaken, a limit of about 15 NTU in otherwise clear waterways should ensure that the upstream migration of some of the most common New Zealand native freshwater species will not be affected.